RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN CALON PENERIMA MANFAAT KEMENSOS DENGAN METODE MFEP BERBASIS WEB (STUDI KASUS DI DESA KENTENG, KECAMATAN BANDUNGAN) - Priyadi Priyadi; Ahmad Zaenudin; Dendy Kurniawan; Indra Ava Dianta; Teguh Setiadi (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
This study seeks to model a decision support information system for determining prospective beneficiaries in Kenteng Village. The settlement method used in this research is the Multi-Factor Evaluation Process (MFEP). In this MFEP method, decision making is done by giving subjective and intuitive considerations to factors that are considered important. then build an information system that can help collect data and propose prospective beneficiaries of the Ministry of Social Affairs in Kenteng Village, as well as test the decision support system. The system in this study was made using CodeIgniter using a mysql database. System design using Flowchart, ERD and UML.